Bar Adsorptive Microextraction Approach for Trace Determination of Local Anesthetics in Urine Matrices - Joana R. P. Pereira; Daniela C. Rocha; Nuno R. Neng; Paulo Maurício; M. Edite Torres; Samir M. Ahmad; Alexandre Quintas (Molecules)
The present work reports the development, optimization, and validation, of a methodology to determine lidocaine, procaine, tetracaine, and benzocaine in urine matrices. Two extractive preconcentration techniques, solid-phase microextraction (SPME) LC Tips and bar adsorptive microextraction (BAμE), were studied and applied to the four target anesthetics, followed by gas chromatography-mass spectrometry (GC-MS) analysis. Several parameters that could affect microextraction and back-extraction were optimized using two different designs of experiments (Box–Behnken and full-factorial) to maximize extraction efficiency from aqueous media. Under optimized experimental conditions, the BAμE technique showed better performance than SPME LC Tips and was chosen for validation assays and urine sample analysis. In blank urine, the BAµE/GC-MS methodology revealed suitable sensitivity (LOD between 2 and 18 ng/mL), good linearity (r2 ≥ 0.9945) between 0.5 and 30.0 µg/mL and recovery yields of 30.3–97.9%. Good precision (%RSD ≤ 8.8%) and accuracy (bias % between −15.9 and 15.0%) values were achieved. The developed methodology was successfully applied to the target anesthetics analysis of volunteers’ urine matrices and proved to be an environmentally friendly alternative to monitor trace levels of local anesthetics in complex matrices compared to other extraction techniques.